IMPLEMENTASI PROGRAM KESEHATAN IBU DAN ANAK BIDANG PELAYANAN ANTENATAL CARE DAN NIFAS DI PUSKESMAS BANDARHARJO KOTA SEMARANG - Fana Nanda Dhevy; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
One indicator of the success of development in the health sector is the maternal mortality rate, this illustrates how the quality of maternal health. Maternal health quality issues are enhanced through maternal and child health programs. Puskesmas as primary health care unit must apply mother and child health program both promotive and preventive treatment based on Ministry of Health Regulation. 75/2014 on Puskesmas and supported by Central Java Governor Regulation No. 17 of 2016 on the implementation of Maternal and Child Health Services in Central Java Province. This study aims to obtain information about the implementation of the rogram as well as factors inhibiting and driving the implementation of Maternal and Child Health Programs in the Field of Antenatal Care Services and Childbed in the Public Health Center Bandarharjo City of Semarang. The method used in this research is descriptive qualitative method. The results of the study on program implementation indicate that antenatal care and postpartum services are good but there are some indicators of antenatal care services that are not optimal such as laboratory test services, pregnancy classes implementation, and counseling. The authors use the six obstacles and drivers of program implementation from Van Metter and Van Horn, which are the size and objectives of the policies, resources, the character of the implementing agency, the attitudes/trends of the implementers, inter-organizational communication and implementation activities, and the economic, social and political environment. Based on the result of the research, the inhibiting factors are the limited number of human resources and the social environment that are less supportive. Based on the results of this research, some efforts are needed to improve the antenatal care and postpartum services, among others, equalization of laboratory tests and pregnant women's classes for all pregnant women, Human resources, and commitment from the government to cooperate in conducting guidance to the community with certain social conditions through socialization and mentoring that can increase knowledge and awareness of the community.